METHODS FOR CALCULATING THE ECONOMIC EFFICIENCY OF NEW TECHNOLOGY (World Economics and Finance Bulletin, 2022)
The article gives a methodology for calculating the economic efficiency of new equipment introduced at the enterprises of JSC "Uzkimyosanoat" and methods for determining the economic efficiency characteristic of the development of specialized production methods and the use of certain types of new equipment. The definition of the national economic effect from the introduction of new technology given in the article is difficult due to objective circumstances and one of the two economic effects has to be taken as the national economic effect. This happens when there is no data on the cost of capital goods and additional capital investments in their production, or there is no data on changes in the reduced costs in the use of new technology.